Passive nihilism and ontotheology: A reply to Husbands on derivative temporality - Austin Hayden Smidt (Finance and Society, 2021)
Conor Husbands' defense and expansion of Elena Esposito's temporality of finance is a much-needed intervention. However, in this response essay, I will show a few of the fundamental weaknesses of Esposito's project, and by extension will highlight some shortcomings of Husbands' defense-expansion. The point is not to dismiss either project; the goal is rather to bring attention to certain philosophical presuppositions that ground both, and that enclose each in what Markus Gabriel would call an ontotheological orientation. In short, Esposito and Husbands operate via an orientation that attempts to think 'the world' as an all-encompassing domain, despite claims to the contrary. How this occurs will be explained below, paying particular attention to the stakes of thinking from such an ontotheological orientation in and to the world. After first presenting Husbands' argument, I develop some critiques of Esposito and Husbands via the work of Suhail Malik, Ray Brassier, Elie Ayache, Jon Roffe, and Quentin Meillassoux. I then open the aperture towards emerging trends in philosophy that contest the foundations upon which Esposito's project is built, in order to suggest more robust readings of finance and society. The work of Sergei Prozorov and Markus Gabriel will be the focus here, but these thinkers merely serve as stand-ins for larger trends in speculative- and neo-realism.
Keywords: 300; Finance; philosophy; temporality; Elena Esposito; ontotheology; nihilism